Hypoglycemic activity of Curculigo latifolia on insulin and glucose uptake activities in in vitro - Ishak, Nur Akmal; Zabidi, Nur Athirah (Medwell Publications, 2019)
Curculigo latifolia (C. latifolia) has been shown to potentiate the antidiabetic and hypolipidemic effects on induced diabetic rats by altering the lipid and glucose metabolisms. In the present study, we evaluated the effect of extracted C. latifolia on in vitro glucose uptake and insulin secretion by adipocyte and investigated muscle and pancreatic cells. The aqueous extracted samples underwent polyphenol assay such as Total Phenolic Content (TPC) and the antioxidant assay to screen the antioxidant activity of extracted samples by inhibition of free radical from DPPH radical. With regard to in vitro, glucose uptake assay was analysed using L6 myotube and 3T3-L1 adipocyte cell lines and insulin secretion was assayed using BRIN-BD11 pancreatic cell in which both assays were examined under different extracted parts of samples investigated. The results indicated that C. latifolia fruit possessed the highest amount of TPC (95 mg GAE/100 g C. latifolia fruit extract) and antioxidant activity as it achieved the lowest IC50 for DPPH assay (1.0±0.1 mg/mL). Cells treated with C. latifolia fruit extract under insulin secretion assay has the highest stimulation compared to others in the following descending order fruit>root>leaf. In addition, C. latifolia fruit extract also showed the highest result in glucose uptake activity by 13 fold at 0.05 mg/mL with insulin presence in 3T3-L1 adipocyte cells. However, in L6 myotube cells, C. latifolia fruit extract increased basal and insulin-mediated glucose uptake activity. The results indicated the presence of antihyperglycaemic from insulin-releasing and glucose uptake activity in C. latifolia. of half-plane increase. Our results are agreeable with the previous works. Keywords: Magnetic nanocomposite; Heavy metal ions; Surface plasmon resonance